2020
DOI: 10.1111/ajt.15917
|View full text |Cite
|
Sign up to set email alerts
|

The association of pretransplant dialysis exposure with transplant failure is dependent on the state-specific rate of dialysis mortality

Abstract: Longer pretransplant dialysis exposure is associated with a higher risk of transplant failure. Whether patients who receive dialysis in a region with a higher rate of dialysis mortality are a higher risk for transplant failure is unknown. Adjusted state‐specific hemodialysis mortality rates were determined in 3‐year intervals among prevalent dialysis patients in the United States between 1995 and 2012. The effect of state‐ and period‐specific dialysis mortality on the association of pretransplant dialysis expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…Yet, as seen in our study, only about one‐quarter (28%) of patients receive a pre‐emptive transplant or have a dialysis duration less than 1.45 years. Policies to decrease these wait times are urgently needed (e.g., expanding the deceased donor organ pool); it remains to be seen if national policies aimed at increasing transplantation (i.e., Advancing American Kidney Health Executive Order in the United States) may help to reduce time on dialysis 38 Furthermore, improvements in dialysis care may also need attention 39 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, as seen in our study, only about one‐quarter (28%) of patients receive a pre‐emptive transplant or have a dialysis duration less than 1.45 years. Policies to decrease these wait times are urgently needed (e.g., expanding the deceased donor organ pool); it remains to be seen if national policies aimed at increasing transplantation (i.e., Advancing American Kidney Health Executive Order in the United States) may help to reduce time on dialysis 38 Furthermore, improvements in dialysis care may also need attention 39 …”
Section: Discussionmentioning
confidence: 99%
“… 11 Mortality among patients who received a transplant after undergoing dialysis for more than 1 year is assumed be higher and increased with time spent receiving dialysis. 14 Fifth, death-censored graft loss in a recipient who has been on dialysis is assumed to be 1.25-fold higher than death-censored graft loss in a preemptive recipient. 11 Sixth, preemptive patient and graft survival is independent of eGFR at the time of transplantation.…”
Section: Methodsmentioning
confidence: 99%
“… 11 For patients transplanted after 1 to 2, 2 to 3, 3 to 4, and 4 to 5 years of dialysis, the values (for those transplanted from the dialysis waiting list) were 1.10, 1.18, 1.24, 1.35, respectively. 14 c Mortality on the dialysis WL modeled to increase with time. 16 Patients transitioning from the preemptive WL to dialysis were modeled to have a higher mortality in the first year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of AJT , Gill et al examine the important issue of whether the association between dialysis vintage and risk of graft loss varies by state dialysis mortality rates 1 . Using data from the United States Renal Data System (USRDS), the authors found that every additional year of dialysis was associated with a 4% higher risk of graft failure in states with the lowest quartile of dialysis mortality but 8% higher risk in states with the highest quartile of dialysis mortality.…”
mentioning
confidence: 99%